Analisis Kebutuhan Belajar Bahasa Arab sebagai Bahasa Asing dalam Konteks Pendidikan Tinggi - Annisa, Maryam Nur; Safii, Randi (ELOQUENCE : Journal of Foreign Language, 2023)
Background:  The importance of foreign language skills in the face of an increasingly connected era of globalization and increasing demand for learning Arabic as an official language in more than 20 countries. Purpose: This study aims to analyze the need to learn Arabic as a foreign language in the context of higher education. Method: The research method used is a qualitative approach with data collection techniques through surveys and interviews with active students of Arabic learning programs and lecturers who teach Arabic. Results and Discussion: The results showed that students have an academic goal to master Islamic religious texts and a professional goal to increase career opportunities in the Middle East and North Africa region. Students' motivations for learning Arabic include religious, cultural, and professional factors. Challenges students face in learning Arabic include the complexity of Arabic grammar and writing systems, lack of opportunities for language practice outside the classroom, and limited learning resources. Lecturers recognize the importance of focusing on developing Arabic communication skills and supporting language practice outside the classroom through social activities. Conclusions and Implications: The conclusions of this study emphasize the importance of developing Arabic learning programs that integrate the language in a variety of communication contexts, improve access to learning resources, create inclusive and innovative learning environments, and provide support in Arabic practice outside the classroom. The implications of this research are expected to increase the effectiveness of Arabic language learning in higher education environments so that students can develop Arabic language skills and understanding of Arabic culture more comprehensively and relevantly in facing the challenges of globalization.